METHODOLOGY OF FORMING STUDENTS' PRAGMATIC COMPETENCE BASED ON CORPUS TECHNOLOGIES - Adizova Nodira Bakhtiorovna (Innovate Conferences, 2025)
In this thesis, a brief description of the methodological models for the formation of students' pragmatic competence based on corpus technologies is given.
Keywords: hierarchy, integrity, structurality, multiplicity, systematicity.